Efficacy and usability of a novel nebulizer targeting both upper and lower airways - Daniela Posa; Antonio Pizzulli; Petra Wagner; Serena Perna; Stephanie Hofmaier; Paolo Maria Matricardi; Susanne Lau (BMC, 2017)
Abstract Background Upper and lower airways diseases share in part their pathogenic mechanisms and frequently occur simultaneously as "United Airway Disease." Local treatment with nebulizers delivers anti-symptomatic drugs in either the upper or the lower airways, according to the particle size generated by the nebulizer. To our knowledge, no nebulizer combines both application ways. The aim of this study is to test the efficacy and usability of a new nebulizer (OMRON A3 complete), generating aerosols with particles diameters of 2-4.5 μm, 4.5-7.5 μm or >7.5 μm, according to the user's choice. Methods Seventy-seven patients between 5 and 17 years of age with a diagnosis of rhinitis or asthma were examined. Oxymetazoline or Salbutamol were prescribed according to best clinical practice guidelines. Both drugs were administered through the OMRON A3 Complete nebulizer, with a particle dimension of >7.5 μm to treat nasal obstruction and 2-4.5 μm for bronchial obstruction. The efficacy of treatment was assessed by total nasal inspiratory airflow and FEV-1, Tiffeneau index (FEV1/FVC) and MMEF 25/75 respectively, 10 min before and after treatment. Symptom improvement and usability were measured by patients' and doctors' questionnaires. Results Overall, 77 patients seeking care for acute respiratory symptoms were assigned to the upper (n = 39) or lower (n = 38) airways disease group. For symptoms of the upper airways, 92% (95% CI, 77-97%) of the patients reported subjective improvement, while 87% (95% CI, 73-94%) did so for the lower airways. The average total nasal inspiratory airflow improved significantly (p = 0.030) among the patients with upper airways symptoms, from 275 ml/s (95% CI, 207-342 ml/s) to 359 ml/s (95% CI, 300-419 ml/s) after Oxymetazoline administration. All selected lung function parameters (FEV1, Tiffeneau Index and MMEF25-75) significantly improved among the patients with lower airways symptoms after inhalation of Salbutamol (p < 0.001). The nebulizer was assessed as "easy to use" by over 95% of participants in both groups. Conclusions The OMRON A3 efficiently delivers anti-symptomatic drugs in both upper and lower airways in a user-friendly way. This device may be useful to facilitate adherence to a complete treatment of respiratory symptoms in patients with symptoms of the so-called United Airway Disease.